Eco-efficiency and financial performance in Latin American countries: An environmental intensity approach - Rodríguez García, Martha del Pilar; Galindo Manrique, Alicia Fernanda; Cortez Alejandro, Klender Aimer; Méndez Sáenz, Alma Berenice (Elsevier Science, 2022)
This research contributes to the literature by empirically demonstrating the economic effect of listed companies’ eco-efficiency in Brazil, Chile, Colombia, and Mexico through an environmental intensity approach. We find evidence of a positive relationship between eco-efficiency and financial performance; that is, a lower CO2 emission-to-sales ratio increases Tobin’s q, with a stronger impact on those companies with the highest financial performance, mainly those in Brazil and Chile, with lower impacts in Colombia. On the other hand, Mexico shows no such relationship. These results can help investors understand the effect of eco-efficiency on Tobin’s q not only at the median but also in the different quantiles. Moreover, our findings help fill the gap in the literature on eco-efficiency at the micro level in Latin American countries.